2020
DOI: 10.1002/advs.202002601
|View full text |Cite
|
Sign up to set email alerts
|

A 3D‐Printed Self‐Adhesive Bandage with Drug Release for Peripheral Nerve Repair

Abstract: Peripheral nerve injury is a common disease that often causes disability and challenges surgeons. Drug-releasable biomaterials provide a reliable tool to regulate the nerve healing-associated microenvironment for nerve repair. Here, a self-adhesive bandage is designed that can form a wrap surrounding the injured nerve to promote nerve regeneration and recovery. Via a 3D printing technique, the bandage is prepared with a special structure and made up of two different hydrogel layers that can adhere to each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Although the American Society for Testing and Materials (ASTM) classifies seven main categories of 3D printing technologies [87], five main technologies have been researched within pharmaceuticals (e.g., binder jet printing [88,89,131,132]; fused deposition modelling, FDM [92,93,[133][134][135]; semi-solid extrusion, SSE [96,97,[136][137][138][139]; selective laser sintering (SLS) [99][100][101][102][103][104]; and vat photopolymerization [109,115,[140][141][142][143]). More recently, there has been a considerable interest in a sixth technology, termed direct powder extrusion (DPE) or melt extrusion deposition (MED™), which reduces risks of thermal drug degradation by simplifying the extrusion procedure into a single-step process [105][106][107]144].…”
Section: D Printing Of Medicinesmentioning
confidence: 99%
“…Although the American Society for Testing and Materials (ASTM) classifies seven main categories of 3D printing technologies [87], five main technologies have been researched within pharmaceuticals (e.g., binder jet printing [88,89,131,132]; fused deposition modelling, FDM [92,93,[133][134][135]; semi-solid extrusion, SSE [96,97,[136][137][138][139]; selective laser sintering (SLS) [99][100][101][102][103][104]; and vat photopolymerization [109,115,[140][141][142][143]). More recently, there has been a considerable interest in a sixth technology, termed direct powder extrusion (DPE) or melt extrusion deposition (MED™), which reduces risks of thermal drug degradation by simplifying the extrusion procedure into a single-step process [105][106][107]144].…”
Section: D Printing Of Medicinesmentioning
confidence: 99%
“…The experimental results showed that the bandage can promote the repair of injured nerves, indicating its potential application in nerve regeneration. [ 57 ] Overall, the single lumen linear hollow conduits are the initial design version of NGCs. [ 58 ] Although hollow NGCs cannot fully meet clinical requirements, they are more clinically acceptable than other types of NGCs.…”
Section: D Printed Nerve Guide Conduits With Personalized Architecturesmentioning
confidence: 99%
“…3D printing technology is a convenient method that can be used to fabricate different morphological NGCs that could influence neural cell proliferation and migration. Additionally, the microstructures of NGCs can also affect the controlled and sustained release of growth factors and drugs to offer specific cues to the regenerating tissues [ 121 ]. Integrating cells, growth factors and drugs into biomaterials to prepare functional NGCs may be a potential strategy to build a more ideal microenvironment for functional recovery of injured nerves.…”
Section: Live Cellsmentioning
confidence: 99%